Anticipación estratégica sobre la Penitenciaría del Litoral prospectiva al 2033 - Chamorro Salinas, Patricio Javier (2022)
Internal violence within a rehabilitation center is a case study that concerns the political sphere, through the intervention of the social rehabilitation system through the governance and decision-making of the SNAI; to the penitentiary sphere, through the management of the deprivation of liberty centers, specifically in this case the Litoral Penitentiary; and, to the field of future studies, as an analytical theoretical instrument, which allows us to use fourth generation Prospective for the application of alternative futures. Regarding the attention to the following factors: governance in social rehabilitation, lack of an adequate prison model; and, to the internal violence of the Litoral Penitentiary, we can indicate that these are intertwined to indicate that the application of guidelines and public policies must occur in order to create a penitentiary model that is capable of eradicating internal violence in the centers of social rehabilitation.